If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -43 = 2(x + 2) + 8 Reorder the terms: -43 + -3x = 2(x + 2) + 8 Reorder the terms: -43 + -3x = 2(2 + x) + 8 -43 + -3x = (2 * 2 + x * 2) + 8 -43 + -3x = (4 + 2x) + 8 Reorder the terms: -43 + -3x = 4 + 8 + 2x Combine like terms: 4 + 8 = 12 -43 + -3x = 12 + 2x Solving -43 + -3x = 12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -43 + -3x + -2x = 12 + 2x + -2x Combine like terms: -3x + -2x = -5x -43 + -5x = 12 + 2x + -2x Combine like terms: 2x + -2x = 0 -43 + -5x = 12 + 0 -43 + -5x = 12 Add '43' to each side of the equation. -43 + 43 + -5x = 12 + 43 Combine like terms: -43 + 43 = 0 0 + -5x = 12 + 43 -5x = 12 + 43 Combine like terms: 12 + 43 = 55 -5x = 55 Divide each side by '-5'. x = -11 Simplifying x = -11
| -5x-13=-28 | | 3w-2(4-8w)=8w+25 | | z^2-z+0.25=0 | | 9=-7-3-a+a | | (9y+11)(4y+5)=0 | | 423/16-281/4 | | 5x+38=4(2x+2) | | 6(5-4v)=2(4v-17) | | -3x+20=23 | | 2(4x+3)+1=2x+49 | | -6x/6 | | -2x-20=3(x+1)-8 | | 2(x+4)=x+3 | | 9x+3y=5 | | 8x^2+42x+49=0 | | 8x-4=4x-40 | | 8(4u-7)-8u=-2(u+2) | | 2x+2/6x^2+16x+10 | | -7x-6=-4x-24 | | a(2)-7a+6=0 | | 144w^2-9=0 | | x^2+xy-x=3 | | Y=6x^2+17x-28 | | (1/2)x+9=10 | | 6n(2)+36n+54=0 | | 4(2x-3)+4x=6(2x+5) | | 24x^2+48-72=0 | | 5-3x+4(x-3)=4 | | 5/9+x=6/18 | | v(2)-6v=0 | | 9.86=X^2 | | (p+5)(7p-8)=0 |